A Comparison of Numerical Strategies for Modeling the Transport Phenomena in High-Energy Laser Surface Alloying Process - Chatterjee, Dipankar (Frontiers in Mechanical Engineering, 2017)
A comparative assessment is done on the effectiveness of some developed and reported macroscopic and mesoscopic models deployed for addressing the three-dimensional thermo-fluidic transport during high power laser surface alloying process. The macroscopic models include the most celebrated k-ε turbulence model and the large eddy simulation (LES) model, whereas a kinetic theory based lattice Boltzmann (LB) approach is invoked under the mesoscopic paradigm. The time dependent Navier-Stokes equations are transformed into the k- turbulence model by performing the Reynolds averaging technique, whereas a spatial filtering operation is used to produce the LES model. The models are suitably modified to address the turbulent melt-pool convection by using a modified eddy viscosity expression including a damping factor in the form of square root of the liquid fraction. The LB scheme utilizes three separate distribution functions to monitor the underlying hydrodynamic, thermal and compositional fields. Accordingly, the kinematic viscosity, thermal and mass diffusivities are adjusted independently. A single domain fixed-grid enthalpy-porosity approach is utilized to model the phase change phenomena in conjunction with an appropriate enthalpy updating closure scheme. The performance of these models are recorded by capturing the characteristic nature of the thermo-fluidic transport during the laser material processing. The maximum values of the pertinent parameters in the computational domain obtained from several modeling efforts are compared in order to assess their capabilities. The comparison shows that the prediction from the k-ε turbulence model is higher than the LES and LB models. Additionally, the results from all three models are compared with the available experimental results in the form of dimensionless composition of the alloyed layer along the dimensionless depth of the pool. The comparison reveals that the LB and the LES approaches are better than the k-ε turbulence approach in reproducing the experimental results.